Cumplimiento de las obligaciones fiscales y su relación con las infracciones tributarias en la empresa ABC SAC - Noa Cayalle, Emely Bertha (2023)
In order to investigate the correlation between tax compliance and tax violations in the company ABC SAC, a quantitative approach was used. This research was based on a non-experimental design of quantitative cross-sectional type, with descriptive and exploratory characteristics. The years selected for the study were 2019 and 2020, in which relevant historical information was collected. In the research, Spearman's nonparametric statistical test of correlation was used with the objective of analyzing the relationship between the variables. The results revealed a highly significant correlation between tax compliance and tax violations (rho = 0.975). Likewise, a close relationship was identified between infractions and the tax payable (rho = 0.962), the latter being influenced by the use of simulated invoices with the purpose of reducing the tax burden. The analysis of the data indicated that compliance with tax obligations is substantially linked to tax violations, a finding that reinforces the thesis of this study. In particular, it was found that the company adopted practices of using simulated invoices, which triggered the commission of tax omission infractions. These results underscore the need for greater vigilance and education in tax matters to encourage responsible fiscal behavior.